DEVELOPING COMMUNICATIVE AND WEB BASED-ENGLISH SYLLABUS FOR ECONOMICS AND BUSINESS STUDENTS - MELATI, MELATI; SYAHRIAL, SYAHRIAL; SOFYAN, DEDI (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
Although the English lecturers have created an English syllabus since they started to teach English based on Higher Education Curriculum, it still needs to cover the needs of economic students. This research aimed: 1) to determine the needs of English learning materials (e.g., English skills, English sub-skills, and topic and themes), develop the learning objectives of communicative and WEB based-English syllabus, and 2) measure the eligibility of communicative and WEB-Based English syllabus for students of Economics. This research was designed as a developmental research that involved thirty-three economic students, four English lecturers, four alumni, and two stakeholders. This research data was gathered from a set questionnaire, interview, and documentation. The results of this research revealed that the students of Economics need integrated English language skills. Then, the communicative approach used in designing the communicative syllabus focuses on communication as the organizing principle for teaching rather than mastering the grammatical structure. Moreover, from the experts' perspective, the communicative and WEB Based English Syllabus eligibility was in a very good category (97.08%). Students could use this developed syllabus to improve their English proficiency. It could optimally solve the problems of a non-existent English course syllabus for economics students' qualification to compete for jobs, the global market, and the ASEAN Economics Community. In conclusion, economic students need English learning syllabus and materials related to their disciplines, and the developed communicative and WEB-based syllabus has been suitable for the economic students' needs in improving their English proficiency.